Kualitas mikrobiologi basis pelembab dari lemak daging Sapi metode low temperature dan bouble boiling berdasarkan angka lempeng total (ALT) - Kurniawati, Triani; Luviriani, Eva; Rahasasti, Indri Dwi; Calyptranti, Rosellynia; Shafly, Alman (Universitas Muhammadiyah Magelang, 2025)
Dry skin is a problem that bothers many people. One of the causes of dry skin is skin dehydration, which can be overcome by using moisturizing cosmetics. Vaseline is a moisturizer commonly used by the public because it does not cause allergies and has good moisturizing capabilities. However, it is derived from non-renewable petroleum, necessitating alternatives. Animal fats can be used as cosmetic moisturizers and are considered safer than chemical substances like zinc oxide. According to BPOM, cosmetic products must pass safety tests such as microbial contamination, heavy metal contamination, and chemical contamination tests. Beef fat contains water and fatty acids that can create a suitable medium for microbial growth. However, temperature and water content affect microbial growth, necessitating further research on the microbiological quality of beef fat using low temperature and double boiling methods. This study aims to determine the microbiological quality of beef fat moisturizer bases using low temperature and double boiling methods through Total Plate Count (TPC) testing. This research is a pre-experimental study with a one-shot case study design. The results show that the TPC values of beef fat using low temperature and double boiling methods are each 1 x 10^4 CFU/g. This indicates that the TPC values of beef fat using low temperature and double boiling methods do not meet BPOM criteria, which is < 500 CFU/g. Keywords: Moisturizer; Beef Tallow; Low Temperature; Double Boiling; Total Plate Count.